Análise das conformidades de uma obra residencial unifamiliar no sistema Light Steel Frame: estruturas de elevação no método por painéis e fechamento vertical das paredes externas de vedação - Melo, Maicon Adans Gonçalves de (My University, 2024)
This work presents a case study with comparison criteria and qualitative analysis of the Light Steel Frame (LSF) constructive system in the panel method and vertical closing of the outer walls. The main objectives will be to investigate the execution of the LSF constructive system, between the interface of the structural elements and installation of the materials of the external walls of sealing, to indicate the conformities and to compare them with the Brazilian technical Norms, among them; ABNT NBR 6355:2012, ABNT NBR 15253:2014, up to the recently released Light Steel Frame standard, ABNT NBR 16970:2022, will also be used as a basis for technical manuals from the Brazilian Center for Steel Construction (CBCA). The object of study is a high standard single-family residence in the city of Caxias do Sul - RS. The methods applied in this course conclusion work can be replicated for different standards of single-family residence in LSF, low, medium and high standard. A case study was carried out from the beginning of the elevations mounted on the raft and specific points in the structure were verified, points that are important to maintain the structural rigidity, and in the external walls of sealing the application of the correct closing materials. The conformities found were satisfactory, with a result above 90%, demonstrating that the work had quality control and attention in the structural execution of the LSF constructive method and used adequate materials and with good technical performance. [resumo fornecido pelo autor]
Este trabalho apresenta um estudo de caso com critério de comparação e análise qualitativa do sistema construtivo Light Steel Frame (LSF) no método por painéis e fechamento vertical das paredes externas de vedação. Os principais objetivos serão de investigar a execução do sistema construtivo LSF, entre interface dos elementos estruturais e instalação dos materiais das paredes externas de vedação, indicar as conformidades e compará-las com as Normas técnicas brasileira, dentre elas; ABNT NBR 6355:2012, ABNT NBR 15253:2014, até a norma recém-lançada de Light Steel Frame, ABNT NBR 16970:2022, serão utilizados também como base os manuais técnicos do Centro Brasileiro da Construção em Aço (CBCA). O objeto de estudo é uma residência unifamiliar de alto padrão na cidade de Caxias do Sul - RS. Os métodos aplicados neste trabalho de conclusão de curso podem ser replicados para diferentes padrões de residência unifamiliar em LSF, baixo, médio e alto padrão. Foi realizado o estudo de caso desde o início das elevações montadas sobre o radier e verificado pontos específicos na estrutura, pontos estes que são importantes para manter a rigidez estrutural, e nas paredes externas de vedação a aplicação dos materiais de fechamento correto. As conformidades encontradas foram satisfatórias, com resultado acima de 90%, demonstrando que a obra teve controle de qualidade e atenção na execução estrutural do método construtivo LSF e utilizou materiais adequados e com bom desempenho técnico. [resumo fornecido pelo autor]
Keywords: Construção Civil; Sustentabilidade